Identification of RD5-Encoded Mycobacterium tuberculosis Proteins As B-Cell Antigens Used for Serodiagnosis of Tuberculosis. (4th June 2012) - Zhang, Miao-Miao; Zhao, Jun-Wei; Sun, Zhan-Qiang; Liu, Jun; Guo, Xiao-Kui; Liu, Wen-Di; Zhang, Shu-Lin
Abstract : Comparative genomic studies have identified several Mycobacterium tuberculosis -specific genomic regions of difference (RDs) which are absent in the vaccine strains of Mycobacterium bovis BCG and which may be useful in the specific diagnosis of tuberculosis (TB). In this study, all encoded proteins from DNA segment RD5 of Mycobacterium tuberculosis, that is, Rv3117–Rv3121, were recombined and evaluated by enzyme-linked immunosorbent assays for antibody reactivity with sera from HIV-negative pulmonary TB patients (n = 60 ) and healthy controls (n = 32 ). The results identified two immunodominant antigens, that is, Rv3117 and Rv3120, both of which revealed a statistically significant antigenic distinction between healthy controls and TB patients (P < 0.05 ). In comparison with the well-known early-secreted antigen target 6 kDa (ESAT-6) (sensitivity 21.7%, specificity 90.6%), the higher detection sensitivity and higher specificity were achieved (Rv3117: sensitivity 25%, specificity 96.9%; Rv3120: sensitivity 31.7%, specificity 96.9%). Thus, the results highlight the immunosensitive and immunospecific nature of Rv3117 and Rv3120 and indicate promise for their use in the serodiagnosis of TB.